2019
DOI: 10.1111/jcmm.14694
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell–derived conditioned medium attenuate angiotensin II‐induced aortic aneurysm growth by modulating macrophage polarization

Abstract: Mesenchymal stem cells (MSCs) exhibit therapeutic benefits on aortic aneurysm (AA); however, the molecular mechanisms are not fully understood. The current study aimed to investigate the therapeutic effects and potential mechanisms of murine bone marrow MSC (BM‐MSCs)–derived conditioned medium (MSCs‐CM) on angiotensin II (AngII)‐induced AA in apolipoprotein E‐deficient (apoE−/−) mice. Murine BM‐MSCs, MSCs‐CM or control medium were intravenously administrated into AngII‐induced AA in apoE−/− mice. Mice were sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 32 publications
(94 reference statements)
3
26
0
Order By: Relevance
“…Reports have shown that a reduction in M1 macrophages and an increase in M2 macrophages improved liver fibrosis both in vivo and in vitro by suppressing the inflammatory cytokines, interleukin (IL)-6 and IL-1b, releasing the antifibrotic factor IL-10, inhibiting the activity of hepatic stellate cells, and increasing the levels of the extracellular matrix degrading enzymes, such as matrix metalloproteinase (MMP)-9 and MMP-12. (22)(23)(24)(25) Griess et al (26) have also reported that M2 macrophages increased the levels of SOD-2, a protein effective against oxidative stress, suggesting that, in the present study, increased M2 macrophages caused an increase in SOD-2 protein, which controlled intrahepatic oxidative stress, thereby reducing the number of 8-OHdG-positive cells in the liver.…”
Section: Discussionsupporting
confidence: 65%
“…Reports have shown that a reduction in M1 macrophages and an increase in M2 macrophages improved liver fibrosis both in vivo and in vitro by suppressing the inflammatory cytokines, interleukin (IL)-6 and IL-1b, releasing the antifibrotic factor IL-10, inhibiting the activity of hepatic stellate cells, and increasing the levels of the extracellular matrix degrading enzymes, such as matrix metalloproteinase (MMP)-9 and MMP-12. (22)(23)(24)(25) Griess et al (26) have also reported that M2 macrophages increased the levels of SOD-2, a protein effective against oxidative stress, suggesting that, in the present study, increased M2 macrophages caused an increase in SOD-2 protein, which controlled intrahepatic oxidative stress, thereby reducing the number of 8-OHdG-positive cells in the liver.…”
Section: Discussionsupporting
confidence: 65%
“…A large number of clinical trials should be conducted to determine the optimal MSC dose and delivery route to improve the survival rate of patients with MI and lay the foundation for solving other problems 78,79 . In addition to their effect in MI, MSCs and MSC-derived extracellular vesicles have important effects on other CVDs, such as aortic aneurysm and atherosclerosis [80][81][82][83][84] .…”
Section: Problems and Prospectsmentioning
confidence: 99%
“…The western blotting analysis was performed as previously described 28 . Briefly, cells/aortic tissue were harvested and homogenized on ice with RIPA (Beyotime Biotechnology P0013B) containing proteinase inhibitor (Complete, EDTA-free protease inhibitor cocktail Tablets provided in EASY pack, Roche, 04 693 132 001).…”
Section: Western Blottingmentioning
confidence: 99%